Socio-demographic co-relates of depression among housewives in rural area of district Ludhiana - ., Urvashi; Girdhar, Sangeeta; Chaudhary, Anurag; Gupta, Sanjay; Monga, Shamim (International Journal Of Community Medicine And Public Health, 2019)
Background: Depression is the most common psychiatric disorder in general practice. It is much more common among women than men, with female/male ratio roughly 2:1. In today’s hectic life, stress is increasing in housewives. Very few data is available on depression among housewives in India. So the present study is aimed to assess the prevalence of depression and study its epidemiological co-relates among housewives aged 18-59 years in rural area of district Ludhiana. Objectives were to assess depression among housewives aged 18-59 years in a rural area and determine the association of depression with socio-demographic co-relates. Methods: This study is a community based cross-sectional study carried out in the field practice area of Department of Community Medicine, Dayanand Medical College and Hospital, Ludhiana, Punjab. 300 subjects were selected by systematic random sampling. Assessment of depression among the housewives was done by using Patient Health Questionnare-9 (PHQ-9). Results: In the present study, 43% of the subjects were found to have depression. Mean age of subjects with depression was found to be 42.4 (±10.3) years. There was an increasing trend of depression among housewives with increasing age (p=0.000). Inverse relationship was found between level of education and depression (p=0.000). Lower socio-economic status was found to be associated with higher rates of depression (p=0.039). Conclusions: Depression was seen to be on higher side among housewives in rural area of Ludhiana. Housewives should be educated about warning signs and symptoms of depression and motivated to avail the primary health care services.